2013
DOI: 10.1371/journal.pntd.0002009
|View full text |Cite
|
Sign up to set email alerts
|

Using Geographical Information Systems to Identify Populations in Need of Improved Accessibility to Antivenom Treatment for Snakebite Envenoming in Costa Rica

Abstract: IntroductionSnakebite accidents are an important health problem in rural areas of tropical countries worldwide, including Costa Rica, where most bites are caused by the pit-viper Bothrops asper. The treatment of these potentially fatal accidents is based on the timely administration of specific antivenom. In many regions of the world, insufficient health care systems and lack of antivenom in remote and poor areas where snakebites are common, means that efficient treatment is unavailable for many snakebite vict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 28 publications
5
65
0
5
Order By: Relevance
“…Approximately 88% of the patients were literate and 63% of them were rural workers. The number of snakebite cases increased during the brightest period of the day, although most venomous snakes have nocturnal habits, which corroborates the results of previous studies 11,[18][19][20] . This study showed that the incidence of snakebites was higher among rural workers aged 20-49 years, affecting especially the lower limbs (Table 2) 1,2,9,25 , and 44 (47.8%) patients used alternative medicine ( Table 3).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Approximately 88% of the patients were literate and 63% of them were rural workers. The number of snakebite cases increased during the brightest period of the day, although most venomous snakes have nocturnal habits, which corroborates the results of previous studies 11,[18][19][20] . This study showed that the incidence of snakebites was higher among rural workers aged 20-49 years, affecting especially the lower limbs (Table 2) 1,2,9,25 , and 44 (47.8%) patients used alternative medicine ( Table 3).…”
Section: Resultssupporting
confidence: 90%
“…This report can be confirmed using the data from the Instituto Brasileiro de Geografia e Estatística (IBGE) 1 . Snakebites frequently occur in the lower limbs primarily due to the lack of use of protective equipment during fieldwork, as reported in previous studies 19, [21][22][23] .…”
Section: Resultsmentioning
confidence: 81%
“…They range, for example, from neurotoxicological aspects [39], immune responses [37], phylogeny, venom composition of diverse species [38], the analysis of geographical information [40] to basic science issues [4143] and public health [44]. Despite the burden of disease caused by snakebite envenoming and the need for increased transnational and national funding, there has been no in-depth scientometric analysis of this topic so far.…”
Section: Discussionmentioning
confidence: 99%
“…For example, GIS has been used to assess populations in Central and South America that need access to anti-venom treatment sites for snakebites 17. Another area for GIS includes the examination of maternity care access 18.…”
Section: Introductionmentioning
confidence: 99%